9 Transition-Metal-Catalyzed Dynamic Kinetic Asymmetric Transformations (DYKATs) and Stereoablative Transformations - Hafeman,N. J.; Sardini, Jr.,S. R.; Bhat,V.; Stoltz,B. M. (Dynamic Kinetic Resolution (DKR) and Dynamic Kinetic Asymmetric Transformations (DYKAT), 2023)
Dynamic kinetic asymmetric transformations (DYKAT) are an extensively utilized class of reactions to construct carbon–carbon and carbon–heteroatom bonds from racemic starting materials. Much like DYKAT, stereoablative transformations grant access to enantioenriched building blocks from racemic substrates. In contrast to DYKAT, stereoablative transformations function via irreversible destruction of the stereocenter rather than a catalyst-promoted epimerization. While this review is not exhaustive, it focuses on transition-metal-catalyzed processes and outlines the current state-of-the-art of this field.
Keywords: Referencework; transition-metal catalysis; asymmetric transformations; DYKAT; stereoablative transformations; enantioselective catalysis; chiral building blocks